2014
DOI: 10.7567/jjap.53.04eg15
|View full text |Cite
|
Sign up to set email alerts
|

Long-period waveguide gratings with amorphous silicon cladding layer on silicon-on-insulator substrates realized by anisotropic wet etching

Abstract: Long-period waveguide gratings (LPWGs) are designed and fabricated on silicon-on-insulator (SOI) substrates with an amorphous silicon (a-Si) layer incorporated as the cladding layer. Specifically, ridge waveguides are etched and patterned on SOI wafers via anisotropic wet etching and a-Si is deposited using a plasma-enhanced chemical vapor deposition (PECVD) system. The experimental results confirm that the resonant wavelengths of LPWG devices are within the range of 1563–1580 nm and that an LPWG ridge wavegui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…SOI substrates have also been used to fabricate photo-diodes and FETs by using a combination of techniques like ion implantation, plasma etching and chemical etching through standard CMOS technology [14,15]. A suspended SOI micro ring resonator has been fabricated using CMOS compatible technology for photothermal spectroscopy [16]. Si waveguides fabricated using standard lithography technique from SOI shows high confinement and nonlinear optical effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…SOI substrates have also been used to fabricate photo-diodes and FETs by using a combination of techniques like ion implantation, plasma etching and chemical etching through standard CMOS technology [14,15]. A suspended SOI micro ring resonator has been fabricated using CMOS compatible technology for photothermal spectroscopy [16]. Si waveguides fabricated using standard lithography technique from SOI shows high confinement and nonlinear optical effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several material systems, including silicon-on-insulator (SOI), silicon, LiNbO 3 and polymers have been used to achieve LP-WGs chip. [9][10][11][12] As a multi-functional material system, polymers exhibit well-controlled refractive indices, highly flexible structures, and large thermo-optic (TO) and electrooptic (EO) coefficients which can be conductive to realizing the monolithic integration with LPWGs-based tunable wavelength filter module. [13,14] At present, some studies have reported polymer LPWGs produced by reactive ion etching (RIE), [15] soft lithography, [16] or induced refractive index modulation.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many high-performance building blocks for Si PICs have been achieved, including passive components, 2,21) modulators, [22][23][24] and photodetectors, [25][26][27] whose performances are almost comparable with those of PICs based on group III-V materials. In a Si PIC, the building components can be interconnected by optical waveguides on the same Si chip so that it becomes much easier to ensure a well-matched optical path length.…”
Section: Introductionmentioning
confidence: 99%